Physicochemical, petrographic and rheologic evaluation of seams 2 and 3 coals from Mina Norte, Guajira municipality, Zulia state, Venezuela. - Escobar, Marcos; Rubio, Jesús (Rev. Téc. Fac. Ing. Univ. Zulia)
The energetic standpoint characterization of seams 2A, 2B, 3A and 3B coals from the Marcelina Formation (Palaeocene) in Mina Norte mine, states that these meet the highest standards in quality ratings using Venezuelan coal companies. Have a high calorific value, low ash and sulphur tenors. His ashes are acid type, which do not cause problems of corrosion or excoriating, and its organic matter has been able to generate liquid hydrocarbons (bitumen). In terms of their potential use in the siderurgical industry, these coals are comparatively low in oxygen, phosphorous and chlorine. This, coupled with its excellent quality, establishing its use as PCI coal (pulverized coal injection in steel manufacturing). Petrography analysis can project its excellent quality as a constituent of steel coking blends; the results of the rheological char- acterization, attest to its excellent plastic character against the temperature increase in non-oxidizing medias, proposing, as it reinforced its qualities with the addition of coke or anthracite fines, or mixed with low-volatile bituminous coal, coke obtained with excellent mechanical strength, suitable for steel or met- allurgical purposes.